NISHA’S JOURNEY FROM RESISTANCE TO SELF-DISCOVERY IN MANJU KAPUR’S HOME - Mitra, Suporna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Within the boundaries of a traditional Indian joint family, Manju Kapur's Home follows the path of Nisha, a young lady negotiating gender expectations, society conventions, and personal goals. Nisha is raised in a world where male privilege controls every element of existence, having been born into a business-focused joint family. Sona, her mother, continuously reinforces traditional gender stereotypes by embodying the idealized position of a devoted wife and homemaker. Nisha internalizes the notion that her value is inferior to that of her male peers from a young age. But Nisha has a rebellious streak, unlike her mother. She raises concerns about how boys and girls are treated differently in the home. Her initial reluctance is clear from her wish for education and independence, but she is repeatedly reminded of the constraints imposed upon her as a woman. This essay explores Nisha's development from an oppressed, resistant person to an autonomous, self-aware lady. The study will examine how Nisha's journey mirrors the larger challenges faced by Indian women in patriarchal homes via the prism of feminist theory. Important topics like gender discrimination, the value of education, personal trauma, love and heartbreak, entrepreneurship, and ultimate self-actualization will all be covered.